Technology Entrepreneurship Project (ENT 600) : Sony Corporation / Fatin Fazliyana Marzuki - Marzuki, Fatin Fazliyana (2021)
SONY Corporation is one of world’s most widely known electronics, gaming, entertainments and financial services markets companies. For this company analysis, it is focusing on the electronic device which are Bluetooth headphone, which is one of the product produced by Sony Corporation to be investigate, identified, evaluate and analysed along with their current problems and come out with solutions. The first problem regarding to their product is the problem with the Bluetooth connection. Customers often complaint regarding to issue where they unable to connect Bluetooth headphones to their device. The main concept of this product is Bluetooth headphone, which the customer should be able to use the headphone freely without need to plug-in any jack in the device. When this issue happened, the consumer will not being able to use the headphone at all as the only way to connect the headphone to the device is only by using Bluetooth. Apart from that, there are another problem regarding to the headphone which are imbalance sound. It happened when one side of the headphone louder or slower than the other side. From the problem state before, there are few solutions to those problems which include improving the manufacturer of the product. The company should focus on using the best product in order to produce great product. Another solution is to do inspection and perform a strict quality control during manufacture and before the company started to market the new product. Inspection should be done, if possible to each product, so that every flaws can be recognized and fixed. Therefore, SONY Corporation should hire more quality control team to make sure this problem can be overcome. All of this solution was consider to help SONY Corporation in produce product with great quality that satisfied their customers.